2017
DOI: 10.1161/jaha.117.006478
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Nitrate in Angina Study: A Randomized Double‐Blind Placebo‐Controlled Trial

Abstract: BackgroundIn this double‐blind randomized placebo‐controlled crossover trial, we investigated whether oral sodium nitrate, when added to existing background medication, reduces exertional ischemia in patients with angina.Methods and ResultsSeventy patients with stable angina, positive electrocardiogram treadmill test, and either angiographic or functional test evidence of significant ischemic heart disease were randomized to receive oral treatment with either placebo or sodium nitrate (600 mg; 7 mmol) for 7 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Our interest in the impact of NO 3 − supplementation on vascular function in the leg began with the observation that NO 3 − supplementation was associated with a decrease in blood pressure [62] and an improvement in exercise tolerance in older adults [22], and in patients with peripheral arterial disease [23,24], heart failure with preserved ejection fraction [47], and stable angina [63]. It was proposed that dietary NO 3 − may enhance plasma NO 2 − , which may increase NO bioavailability [31].…”
Section: Discussionmentioning
confidence: 99%
“…Our interest in the impact of NO 3 − supplementation on vascular function in the leg began with the observation that NO 3 − supplementation was associated with a decrease in blood pressure [62] and an improvement in exercise tolerance in older adults [22], and in patients with peripheral arterial disease [23,24], heart failure with preserved ejection fraction [47], and stable angina [63]. It was proposed that dietary NO 3 − may enhance plasma NO 2 − , which may increase NO bioavailability [31].…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography monitoring revealed that ST-segment depression in the precordial leads and a heart ultrasound had uncoordinated ventricular wall motion. These symptoms were relieved when the dobutamine infusion was interrupted or when inorganic nitrates were used [18]. However, ST-segment depression was not observed in other patients with LAD or LCX disease who also had chest tightness.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary nitrate was associate with small but significant improvements in FMD, PWV and platelet aggregation CHD Schwarz (111) Seventy patients with stable angina (108) Twenty coronary artery disease patients on clopidogrel therapy (122) Nine patients with heart failure R, CO, P, DB BJ (2 h) Nitrate-free BJ Physical performance, clinic resting and exercise BP Inorganic nitrate increased peak knee extensor power but did not modify BP Eggebeen (123) Twenty patients with heart failure with preserved ejection fraction (124) Seventeen patients with heart failure with preserved ejection fraction (113) Eight patients with heart failure with reduced ejection fraction R, CO, P, DB BJ (2 h) Nitrate-free BJ Physical performance, clinic resting and exercise BP Dietary nitrate improved muscle performance but did not have an effect on resting and exercise BP Shaltout (121) Nineteen patients with heart failure with preserved ejection fraction in both human subjects and experimental animals (106,107) . Two studies have found a positive effect of dietary NO − 3 supplementation on platelet aggregation in hypercholesterolaemic patients (94) and platelet-derived extracellular vesicles in coronary artery disease patients on clopidogrel therapy (108) .…”
Section: Therapeutic Effects Of Inorganic Nitrate In Patients With Cvdmentioning
confidence: 99%
“…Moreover, low-dose sodium attenuated myocardial ischaemia and vascular reperfusion injury in a human experimental study ( 110 ) . However, Schwarz et al ( 111 ) showed that supplementation with sodium marginally improved exercise performance in patients with chronic angina on prescribed medications. Conversely, positive effects of dietary supplementation were found on exercise tolerance and onset of claudication intermittens in eight patients with peripheral arterial disease ( 112 ) .…”
Section: Factors That Impair Endothelial Function With Ageingmentioning
confidence: 99%
See 1 more Smart Citation